Formation of Students’ Motivational Readiness for Their Future Professional Activities - Nikolayevna Bedenko, Nadezhda; Borisovna Bakhtigulova, Lyudmila; Viktorovich Kaftan, Vitaliy; Viktorovna Poliakova, Iana; Yevgenievich Klychkov, Kirill (Opción)
Introduction. The process of personal formation of a professional begins from the moment of choosing a profession and lasts throughout the entire professional life of a person, during which the most important problems of the relationship between a person and profession are identified. Research Methodology. In the psychology and pedagogy of Western countries, the problem of motivation for activity is revealed in a number of concepts and theories from various positions. Currently, motivation as a mental phenomenon is interpreted differently. The main theories of motivation should be divided into two areas: content theories that consider motivation from structural positions, and procedural (process-based) theories that consider motivation as a dynamic entity. These areas are united by the understanding of motivation as a secondary (subordinate) to the motive of education. Research results. The notion of “readiness” for activity is considered as an active-effective state of a personality, a psychological pattern of behavior, and mobilization of forces to accomplish a certain task. In the structure of individual professional readiness, researchers distinguish different components, among which the most important is motivational, i.e. attitude to the profession, need to complete the task successfully and interest in the activity. An essential component of professional readiness is psychological readiness,which should be regarded as a complex functional, psychological and personal construct, including positive attitude to a particular type of activities; traits of character and temperament adequate to the requirements of activity; necessary knowledge, skills, habits; sustainable professionally important features of cognitive and emotionalvolitional processes. Discussion. The model, developed for the formation of positive motivation for professional activities in terms of reinforcement and motivation, is based on the following principles: taking all types of personal needs into account and considering real contribution of each employee to the final result. Practical training plays the most important part in the formation of students’ motivational readiness for their professional activities. Conclusion. Well-formed internal motives of students (desire for selfrealization in the activities, motivation for success and willingness to take risks) could serve as the indicators of students’ motivational readiness for professional activities.